Involvement of Macrophage Inflammatory Protein-1 Family Members in the Development of Diabetic Neuropathy and Their Contribution to Effectiveness of Morphine - Rojewska, Ewelina; Zychowska, Magdalena; Piotrowska, Anna; Kreiner, Grzegorz; Nalepa, Irena; Mika, Joanna (Frontiers in Immunology, 2018)
Current investigations underline the important roles of C–C motif ligands in the development of neuropathic pain; however, their participation in diabetic neuropathy is still undefined. Therefore, the goal of our study was to evaluate the participation of macrophage inflammatory protein-1 (MIP-1) family members (CCL3, CCL4, CCL9) in a streptozotocin (STZ)-induced mouse model of diabetic neuropathic pain. Single intrathecal administration of each MIP-1 member (10, 100, or 500 ng/5 μl) in naïve mice evoked hypersensitivity to mechanical (von Frey test) and thermal (cold plate test) stimuli. Concomitantly, protein analysis has shown that, 7 days following STZ injection, the levels of CCL3 and CCL9 (but not CCL4) are increased in the lumbar spinal cord. Performed additionally, immunofluorescence staining undoubtedly revealed that CCL3, CCL9, and their receptors (CCR1 and CCR5) are expressed predominantly by neurons. In vitro studies provided evidence that the observed expression of CCL3 and CCL9 may be partially of glial origin; however, this observation was only partially possible to confirm by immunohistochemical study. Single intrathecal administration of CCL3 or CCL9 neutralizing antibody (2 and 4 μg/5 μl) delayed neuropathic pain symptoms as measured at day 7 following STZ administration. Single intrathecal injection of a CCR1 antagonist (J113863; 15 and 20 μg/5 μl) also attenuated pain-related behavior as evaluated at day 7 after STZ. Both neutralizing antibodies, as well as the CCR1 antagonist, enhanced the effectiveness of morphine in STZ-induced diabetic neuropathy. These findings highlight the important roles of CCL3 and CCL9 in the pathology of diabetic neuropathic pain and suggest that they play pivotal roles in opioid analgesia.